PENEGAKAN HUKUM MELALUI PENDEKATAN RESTORATIVE JUSTICE DALAM PENYELESAIAN PERKARA TINDAK PIDANA OLEH KEJAKSAAN NEGERI BULUNGAN - Syafruddin Syafruddin; Muhamad S. Mae (Universitas Borneo Tarakan, 2022)
AbstractThe purpose of the research is to analyze the process of law enforcement in the settlement of criminal cases by the Bulungan District Prosecutor's Office through a restorative justice approach that can provide justice for the litigants. To analyze the effectiveness of the settlement of criminal cases by the Bulungan District Prosecutor's Office through a restorative justice approach. The research method used is a type of normative legal research. The basic argument for establishing this research as normative legal research is that this research is a type of legal research by studying the norms in laws, generally by moving on to (empirical) field studies that look at social reality about how the application of the law itself is in- concreto.The results of the study show that in essence the process of law enforcement in the settlement of criminal cases by the Bulungan District Prosecutor's Office through a restorative justice approach can provide justice for the litigants, namely the perpetrators of the crime, the victims, also the victims' families or other parties who have an interest in the case. The context of justice within the framework of the restorative justice approach is proportionality justice which provides a balance of restoring the interests of the perpetrators of crimes and victims. The perpetrators of crimes will be restored to their rights as before, no longer placed as former perpetrators of crimes, while the victims will receive restitution for the losses they have suffered as a result of the actions of the perpetrators. The settlement of criminal cases by the Bulungan District Prosecutor's Office through a restorative justice approach, based on research results, has been effective, in the context of restoring the rights of perpetrators and victims, which can be seen in terms of the active participation of both parties to find common ground peacefully in resolving criminal cases, so as to enable victims, perpetrators, families and communities to pay attention to losses due to criminal acts.Keywords: Restorative Justice, Criminal Cases, Bulungan District Attorney